A new isomalabaricane from Vietnamese marine sponge Petrosia ingricans - Kiem, Phan Van; Quang, Ngo Van; Nhiem, Nguyen Xuan; Thuy Hang, Dan Thi; Tuan Anh, Hoang Le; Yen, Pham Hai; Dung, Duong Thi; Cuc, Nguyen Thi; Minh, Chau Van; Mai Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2015)
A new isomalabaricane triterpene, nigricanic acid A (1), and two known compounds (24S)-ergostane 3β,5α,6β,25-tetraol-25-monoacetate (2) and (24S)-ergostane-1β,3β,5α,6β,25-pentaol-25-monoacetate (3), was isolated from Vietnamese marine sponge Petrosia nigricans. Their structures were determined on the basis of 1D and 2D-NMR spectra and HR-ESI-MS, and in comparison with the reported data. The cytotoxicity of all compounds were evaluated by MTT assay on four human cancer cell lines, including Hep-G2, KB, LU-1, and MCF-7. As the results, compound 1 exhibited moderate cytotoxic activity on the four human cancer cell lines with IC50 values ranging of 15.47÷19.34 μg/mL.